Comparison of stress, burnout and its association among postgraduate orthodontic and undergraduate students in India - VenkateshNettam; Prasad Mandava; Gowri SankarSingaraju; Vivek Reddy Ganugapanta; Harsha Yelchuri; RevathiPeddu (Wolters Kluwer Medknow Publications, 2018)
Aim and Objectives: Stress and burnout are the wave of the present decade and dentists and dental specialists are found repeatedly on top of the charts of the more stressed occupation; however, the prevalence among orthodontic postgraduates in India has not been well researched. The present study aimed to investigate the stress and burnout levels of postgraduate students of orthodontics in India. Materials and Methods: A descriptive, cross-sectional study was conducted to evaluate stress and burnout in postgraduate students of orthodontics in India. A stratified randomized sampling method, with stratification as North, East, West, South, and central population was employed. A questionnaire format formulated by the International Stress Management Association, including Maslach burnout inventory was filled by each of these individuals. Results: A total of 284 individuals showed significance for stress and personal accomplishment (PA) (P < 0.05) whereas statistically insignificant for genders. There is statistically significance for geographical distribution to depersonalization and PA. The Pearson's correlation is positive for stress and components of burnout in postgraduates and is negative for undergraduates. Conclusion: This study was the first of its kind to explore stress, burnout, and its association among orthodontic postgraduate students and undergraduates in the country. There are significant levels of stress and burnout in both undergraduates and postgraduates. There is a statistically significant positive correlation to the components of burnout found in postgraduates. These findings may help orthodontic community in planning, management, and prevention of stress and burnout.